Canto coral no Brasil: desafios de possibilidades de uma notação musical alternativa - Silva, Wender José Dalto da (2023)
With the advancement of music technology, the ease of using music anywhere, by anyone, regardless of formal musical training has also progressed - premises that are present in Ubiquitous Music (UbiMus). In this context, it is understood that many individuals, although musical, are not professional musicians or have not had academic study of music and its definitions, such as musical notation and techniques. Therefore, this dissertation presents a bibliographic research on the use of conventional musical notation in choral singing in Brazil, presenting didactic musical tools that are used in choirs and music lessons. Finally, an alternative musical notation called "Letratura" is presented, where there is no need to study sheet music and its specifications, with the aim of assisting singers and teachers in choirs, within the principles of UbiMus to make music accessible to anyone.